How Body Image Can Influence a Woman's Perception of Menopause. Issue 4 (19th May 2021) - Herzig, Lisa; George, Gretchen; Watson, Kaitlynn
Abstract: In a women's life, the universal sign of aging is menopause. This biological experience can be viewed as a women's rite of passage into the next chapter of life. This change affects each person differently, due to a number of adverse symptoms that are felt, creating a stigma. Further, numerous women experience poor body image, which can overall affect their livelihood. However, women with a positive body image, are more likely to view menopause as a positive experience. With that said, it is clear that the healthcare field needs to create a way to support a women's journey into aging.